LEGAL CASE AND HEALTH PERSPECTIVE OF BULLYING LEADING TO BLINDNESS - Suyanto Suyanto; Siti Nur Qomariah; Yuanita Syaiful; Lilis Fatmawati (EQUALEGUM International Law Journal, 2023)
Background. Bullying has a negative impact on both the perpetrator and the victim. The biggest impact is experienced by victims of bullying. Victims of bullying experience physical or psychological disorders. The purpose of this study was to explain a legal case and health perspective of bullying leading to blindness. Research Method. This research was a case report. One case of bullying happened in an elementary school in Gresik. The victim (SAH, 8 years old) was a girl who experienced blindness as a result of bullying by her friends at her school. Findings. On August 7, 2023, SAH was poked in the right eye by a student because he was reluctant to give money. From that incident, SAH's right eye became blind. The incident took place in the hallway inside the school. The bullying happened 1 year ago and continued until SAH became blind. Seeing the case that occurred at an elementary school in Gresik, there was a connection with Law No. 35 of 2014 concerning child protection. Bullying in this case have an impact on physical disorder and psychological disorder for the victim. Conclusion. There has been an appeal for bullying in the school environment from the Ministry of Education and Culture. The region has even launched anti-bullying. Prevention efforts and literacy regarding bullying are the school's responsibility.